Epidemiological investigations of Shiga toxin-producing Escherichia coli (STEC) O157 And STEC O26 in New Zealand slaughter cattle, and the source attribution of human illness : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Veterinary Science at Massey University, Palmerston North, New Zealand - Jaros, Patricia (Massey University, 2014)
Shiga toxin-producing Escherichia coli O157:H7 (STEC O157) and related non-O157 STEC strains are enteric pathogens of significant public health concern worldwide, including New Zealand, causing clinical diseases ranging from diarrhoea and bloody diarrhoea to the life-threatening haemolytic uraemic syndrome. Cattle are considered the principal hosts and have been shown to be a source of STEC infection for both foodborne and environmental outbreaks of human diarrhoeal disease overseas. A series of observational studies were conducted to gain knowledge on the epidemiology of STEC O157 and STEC O26 in New Zealand slaughter cattle and assess the relative importance of cattle as a source of domestically-acquired STEC infections in humans. A repeated cross-sectional study conducted on four selected New Zealand beef slaughter plants provided detailed data on the prevalence and concentration of faecal shedding of STEC O157 and STEC O26 in 695 very young calves (4–7 days-old) and 895 adult cattle post-slaughter, identifying calves as more prevalent carriers of STEC. Findings of a subsequent cohort study, the first of its kind, provided evidence that for the 60 calves examined, transportation and lairage was not associated with increase of faecal shedding of E. coli O157 and O26 (STEC and non-STEC) but increase of cross-contamination of hides and carcasses post-slaughter. In a national prospective case-control study, 113 STEC cases and 506 random controls were interviewed for risk factor evaluation. The study findings implicate that environmental and animal contact, but not food, as significant exposure pathways for sporadic STEC infections in humans in New Zealand, and suggest ruminants as the most important source of infection. The molecular analysis of bovine and human STEC O157 isolates provided evidence for the historical introduction of a subset of the globally-circulating STEC O157 strains into New Zealand and ongoing localised transmission of STEC between cattle and humans. These findings will contribute to the development of a risk management strategy for STEC, similar to those already implemented for Campylobacter, Salmonella, and Listeria, which pose a high risk to public health and New Zealand’s access to international markets. Furthermore, risk factors identified in the case-control study will contribute to the design of public health interventions to reduce the incidence of STEC infections in New Zealand.
Keywords: Escherichia coli infections in animals; Cattle; Escherichia coli infections; Epidemiology; New Zealand; Research Subject Categories::VETERINARY MEDICINE::Veterinary epidemiology